A CRITICAL REVIEW OF THE NUTRITIONAL AND PHARMACOLOGICAL PROPERTIES OF ELETTARIA CARDAMOMUM (L.) - Sowmya K M, R T Narendhirakannan (Chelonian Research Foundation, 2023)
For thousands of years, natural plant products have been the cornerstone of medicinal medicines due to their distinct pharmacological activities and structural variety. For millennia, people have employed natural plant products like spices as food flavorings and preservatives. Furthermore, from ancient times, spices have been utilized in medicine due to their known and assumed health benefits. Spices are essential for everyday health maintenance during a period of recurrent pandemics because they balance the "humors" in diet. The significance of selecting a spice now arises. "Elettaria cardamomum" is a well-known spice that has been used for flavoring numerous food preparations since ancient times. It is also known as Elaichi or cardamom. In addition to its strong therapeutic qualities, it has long been utilized as a folk cure for renal and digestive problems, lung and pulmonary tuberculosis, teeth and gum infections, and other ailments. This review offers data from the literature and evidence about the phytochemical components, bioactive substances, therapy of different ailments, and pharmacological effects of Elettaria cardamomum. Numerous investigations have demonstrated the biological activity of E. cardamomum and its polyphenols, which include metabolic regulation, antioxidant, anti-tumor, and anti-inflammatory properties.Elemimelon has abundant amounts of bioactive components, including limonene, α-terpinyl acetates, and 1,8-cineole and its esters. The current understanding of E. cardamomum's possible pharmacological effects and its usage in the pharmaceutical sector to develop innovative medications to treat a range of illnesses are the main topics of this review. KEYWORDS: Elettaria cardamomum, natural products, nutraceuticals, pharmacological effect, therapeutic.